La Salud Pública en el Ecuador de la Revolución Ciudadana - Aguilar Velasco, Hugo Marcelo (2017)
In these last years of government, healthcare has been an important symbol of the management of the government of the Revolución Ciudadana. The enormous growth of the health care network stands out, with the increase of hospitals and health centers, many of them equipped with important technology, the inclusion in medical attention to other important social sectors, the significant growth of health personnel and the adoption of the Integral Family and Community Health Care Model (MAISFC). Despite this, the health indicators did NOT improve, and the main morbidity and mortality problems were NOT solved. There was a deterioration in the working conditions of health workers, and a breakdown in relations between public and private public health actors